Endometriosis-Associated Macrophages: Origin, Phenotype, and Function - Hogg, Chloe; Horne, Andrew W.; Greaves, Erin (Frontiers in Endocrinology, 2020)
Endometriosis is a complex, heterogeneous, chronic inflammatory condition impacting approximately 176 million women worldwide. It is associated with chronic pelvic pain, infertility and fatigue, and has a substantial impact on health-related quality of life. Endometriosis is defined by the growth of endometrial-like tissue outside the uterus, typically on the lining of the pelvic cavity and ovaries (known as ‘lesions’). Macrophages are complex cells at the centre of this enigmatic condition; they are critical for the growth, development, vascularisation and innervation of lesions as well as generation of pain symptoms. In health, tissue-resident macrophages are seeded during early embryonic life are vital for development and homeostasis of tissues. In the adult, under inflammatory challenge, monocytes are recruited from the blood and differentiate into macrophages in tissues where they fulfil functions, such as fighting infection and repairing wounds. The interplay between tissue-resident and recruited macrophages is now at the forefront of macrophage research due to their differential roles in inflammatory disorders. In some cancers, tumour-associated macrophages are comprised of tissue-resident macrophages and recruited inflammatory monocytes that differentiate into macrophages within the tumour. These macrophages of different origins play differential roles in disease progression. Herein, we review the complexities of macrophage dynamics in health and disease and explore the paradigm that under disease-modified conditions, macrophages that normally maintain homeostasis become modified such that they promote disease. We also interrogate the evidence to support the existence of multiple phenotypic populations and origins of macrophages in endometriosis and how this could be exploited for therapy.